Plant elements reinforcing the sense of place identity of the Muslim Malay Royal Town - Mohd Khalid, Intan Khasumarlina; Ismail, Nor Atiah; Mohd Tahir, Osman; Ismail, Noor Hayati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Due to a lack of secure identity following the new developments in a Muslim Royal Town of high-tech modernization in the twentieth century, the craft maker created any motif with an unknown purpose. As a result, the original character of the location will be tarnished, and the image will vanish. This paper aims to identify the qualitative responses of the plant elements reinforcing the Muslim Royal Town of Kuala Kangsar, conducted semi-structured interview participants based on purposive sampling, including professionals, policymakers, and skilled practitioner's categories. The data was analyzed through qualitative coding using Atlas ti 8.0. The significant findings reveal that the flower, the color related to the flag, leaf, and types of plant, tendril/ meandering cloud, the shape of the plant, and an element of the plant on a Perak Coat of Arm reflected the royal Muslim town. This finding contributes to assessing the details of the plants' motif representation to assist the city council in preserving the unique and valuable historical heritage for the place image of the Muslim Royal Town of Kuala Kangsar, Perak.